Pengembangan Aplikasi Modul Interaktif Chemistry Magazine Dengan Teknologi Augmented Reality Pada Materi Termokimia Kelas XI SMA/MA Berbasis Android - Muhammad Syafii; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Chemistry is considered a science that is quite difficult and uninteresting to learn for many students. One of the causes is the lack of interest in the student's attention to the learning process in chemistry. The use of information and communication technology is an effective and efficient way to improve the quality of the learning process and outcomes in schools. A learning media is created in which modules with magazine models are combined with an Augmented Reality (AR) technology application to facilitate the students to understand the subject matter, especially chemistry. This application implements the Marker Based Tracking and Markerless Augmented Reality methods. Some application design stages are such as collecting data about modules, interface design, database, information displayed, and building applications into Android package (Apk). The tools such as Unity 3D, Vuforia Object Scanner, Vuforia SDK, Android SDK, Java Development Kit, Adobe Photoshop, and Adobe Premiere Pro are used to build this application. The result shows that the Androidbased Augmented Reality application can successfully display more information on the modules that are available in the form of videos about the additional explanation of the thermochemical material. Keywords: Augmented Reality, Marker Based Tracking, Markerless Augmented Reality, Learning Modules, Thermochemistry.